Fighting fires - Simon, Seymour (San Francisco, Calif. : SeaStar Books, 2002)
Presents information about the vehicles and equipment used to fight fires from the ground, sea, and sky.
"Grades P-1"--Cover.
3.1
K-3
Keywords: Fire extinction -- Juvenile literature; Fire extinction; Fire fighting